2022
DOI: 10.1177/17455057221095246
|View full text |Cite
|
Sign up to set email alerts
|

A survey of women’s experiences of using period tracker applications: Attitudes, ovulation prediction and how the accuracy of the app in predicting period start dates affects their feelings and behaviours

Abstract: Introduction: Using an online survey, the aim of this study was to ask women about their real-life experiences of using period tracker apps, their attitudes towards using their app, the information the app provided regarding ovulation and how the accuracy of the app in predicting period start dates affects their feelings and behaviours if their period comes earlier or later than predicted. Methods: This mixed-methods observational study was conducted by an online survey of 50 multiple-choice and open-ended que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…There may be disadvantages to this method, including reporting errors, the need to recall dates concerning menstruation, and cycle irregularity, which may affect the accuracy of predicting the next cycle dates [3,4]. One study of 330 female individuals found that periodic tracking apps had made errors in predicting periods, with 57% (n=189) of female individuals having experienced an earlier period than estimated, while 72% (n=238) had a delayed period relative to what was anticipated [5]. Some reviews have also critiqued menstrual cycle-tracking apps for lacking evidence of their efficacy at times [1].…”
Section: Overviewmentioning
confidence: 99%
“…There may be disadvantages to this method, including reporting errors, the need to recall dates concerning menstruation, and cycle irregularity, which may affect the accuracy of predicting the next cycle dates [3,4]. One study of 330 female individuals found that periodic tracking apps had made errors in predicting periods, with 57% (n=189) of female individuals having experienced an earlier period than estimated, while 72% (n=238) had a delayed period relative to what was anticipated [5]. Some reviews have also critiqued menstrual cycle-tracking apps for lacking evidence of their efficacy at times [1].…”
Section: Overviewmentioning
confidence: 99%
“…Calendars are widely used to support tracking the menstrual cycle in menstrual health interventions, with apps gaining popularity where people can access the internet (Broad et al 2022;Karasneh et al 2020;Schantz et al 2021;Montgomery et al 2012;Oster and Thonton 2011). Such methods support people to know when they will menstruate and better understand the premenstrual syndrome and any changes in the menstrual cycle (Worsfold 2021).…”
Section: Evaluation Of the Veivanua Campaignmentioning
confidence: 99%
“…With the emergence of digital health technologies, accurate at-home hormone tracking has become more accessible and convenient [ 22 , 23 ]. Oova is a testing system that allows users to track their luteinizing hormone and pregnanediol-3-glucuronide (PdG) fluctuations throughout their cycles.…”
Section: Introductionmentioning
confidence: 99%